Medical imaging - Sanjay, H. S.; Niranjanamurthy, M. (Newark : John Wiley & Sons, Incorporated, 2023)
Medical imaging is one of the most important diagnostic tools in healthcare. More than 50% of the clinical market depends on diagnostic imaging to identify different pathological conditions in subjects. It is, therefore, essential for healthcare personnel and paramedical staff as well as the technicians and the supporting engineers to understand the basics of medical imaging. This subject is of utmost importance to every individual involved in the healthcare industry, right from research and development until application and service. Medical Imaging presents the salient aspects of diagnostic imaging modalities. The subjects that are covered are the basic functional principles, the concepts involved, the instrumentation-based aspects, applications, and the latest trends in imaging modalities. This book concentrates on X-rays imaging, computer tomography-based imaging, ultrasound techniques, radionuclide imaging, MRI techniques, and other important diagnostic modalities which are commonly used for medical diagnosis of various pathologies in human beings
Includes index.
Keywords: Diagnostic Imaging; Electronic books